The Application of Multimedia Technology in Social Media Content Marketing. Issue 3 (October 2020) - Ding, Taiyan; Zhu, Kejing
Abstract: With the continuous discussion and dissemination of social media, the rapid growth of content marketing has begun to enter the public's vision. By generating new content and new topics, users and users have a resonance, which attracts attention and carries out content marketing. Starting from the characteristics of content marketing in social media, This article takes multimedia technology in social media content marketing as an example, and analyzes content marketing in social media from three aspects.